Carbon Nano Fibre Reinforcements In Concrete - Awan, Maqbool S; Ali, Arshad; S, Perviz; Awan, Yousaf S (Indonesian Journal of Science and Technology, 2019)
Graphite nanomaterials offer distinct advantages over micro-scale reinforcing fibers in terms of engineering properties and geometric attributes. Thorough dispersion and effective interfacial interactions through proper functionalization of carbon nanofibers are the prerequisites for their effective use in high performance cementitious matrices. Furthermore, use of nano- and micro-scale reinforcements together provides reinforcing effects at different scales, thus rendering balanced gains in engineering properties of the matrix. However, their use in coarser high-performance matrices has not been evaluated thoroughly. The results show improvements in all flexural attributes, impact and abrasion resistance of DSP concrete with addition of 0.16 vol.% of oxidized and poly-acrylic acid physisorbed carbon nanofibers, over the corresponding properties of plain matrix. The results also point to synergetic effect of hybrid reinforcements in improving the various engineering properties of DSP concrete matrix, especially with low modulus polypropylene microfibers.